Influence of strontium containing fluorophosphate glass onto structural and mechanical behavior of MTA network. (April 2023) - Lunawat, Kuhu; Kavitha, S.; Rajkumar, G.; Dhivya, V.; Ravi Kumar, N.; Mahalaxmi, S.; Shaik, Fayaz Ahmed
Abstract: Objective: This study aimed to evaluate the effect of incorporation of strontium based fluoro phosphate glass (SrFPG) 48P2 O5 –29CaO–14NaO–3CaF2 –6SrO on physico chemical and biological properties of mineral trioxide aggregate (MTA). Methods: Optimized SrFPG glass powder were prepared using planetary ball mill and incorporated into MTA in varying proportion (1, 5, 10 wt%) to obtain SrMT1, SrMT5, SrMT10 bio-composite respectively. The bio-composites were characterized using XRD, FTIR and SEM-EDAX before and after soaking for 28 days in stimulated body fluid (SBF) solution. To assess the mechanical properties and biocompatibility of the prepared bio-composite, density, pH analysis, compressive strength and cytotoxicity evaluation using MTT assay were done before and after soaking for 28 days in SBF solution. Results: A nonlinear variation in compressive strength and pH values was noted. Of the bio-composites, SrMT10 was evidenced with rich apatite formation in XRD, FTIR and SEM with EDAX analysis. MTT assay showed increased cell viability in all the samples before and after in vitro studies.